INSTITUTE OF ENHANCED COOPERATION IN EUROPEAN UNION LAW - EXPECTATIONS AND ACHIEVED RESULTS - Dragišić, Radmila (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The Institute of Enhanced Cooperation got its contractual basis in Amsterdam, while it was made more flexible and operational only in Lisbon. Its main purpose was to overcome the blockages in the law-making process, as well as to deepen the integration in the corpus of issues for the member states that wanted it. Through the analysis and a number of legal acts that were adopted within the institute, we can say that it has only partially justified its contractually defined role. Viewed from the perspective of the legal order of the Union as a whole, the particularity of the application of the institute, which ultimately has different solutions in the member states on certain issues of particular importance for legal and natural persons in the Union, requires special attention. Because, no matter how many opportunities the institute of enhanced cooperation provides to the member states in terms of realizing or deepening their cooperation in certain issues, its application, if it does not represent only a stage on the way to establishing general, common rules for all member states, can represent a contradiction and a serious challenge for some of the basic legal principles on which the European Union rests and which the Court of Justice of the European Union has continuously strengthened and expanded. Here, above all, we mean the principle of the uniqueness of its legal order, the principle of prohibition of discrimination on the basis of citizenship and the principle of legal certainty.